Innovation and Evidence for Achieving TB Elimination in the Asia-Pacific Region - DuCros, Philipp; Hussain, Hamidah; Viney, Kerri (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The World Health Organization's (WHO) END-TB strategy has set the world on course to climb the highest of medical mountains by 2035, with a targeted peak of reductions in TB deaths by 95%, TB cases by 90%, and no burdens of catastrophic expenses on families due to TB. Eliminating TB in the Asia-Pacific region, which has 62% of all estimated TB patients globally, will require innovation, rigorous research, and sustained investment. This special issue connects original research and viewpoints on pertinent approaches for improving TB care and prevention in the Asia-Pacific region.